Dampak Media Audio Visual Terhadap Perkembangan Kognitif Pada Anak Kelompok B KB Al Muhajirin Banyuasin 1 Tahun 2023 - Damayanti, Melisa; Effendi, Darwin; ., Padilah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of audio-visual media on the cognitive development of group B children in KB Al Muhajirin Banyuasin 1 Year 2023. The examination strategy used in this study was an exploratory technique. Collecting data in this study using observation, pretest and posttest, as well as documentation. Data analysis used the data normality test and homogeneity test. From this study, it was found that audio-visual media had an impact on cognitive development in children in group B at KB Al Muhajirin Banyuasin 1. This can be concluded based on the increase in results seen between the pretest and posttest conducted in group B1.